Factors Influencing the Success of the Information Systems Strategic Planning at Higher Educational Institutions in Indonesia - Bernadus, Gunawan Sudarsono (2023)
This study focuses on the proposed development of a successful model of Information Systems Strategic Planning (ISSP) at Higher Education in Indonesia and its evaluation. In the current era of uncertainty in the evolution of ISSPs, complete ISSP success factors are needed. This research was conducted because at that time the success model of ISSP in Higher Education in Indonesia was only determined by the success factors, which are partial in number, namely only one factor and are considered incomplete. The methodology to solve this problem is carried out by adopting a combination of the 2003 Delone and McLean model whose forming factors have been modified, namely Planning System Quality, Product Quality, System Delivery Quality, Use, Satisfaction, and ISSP Net Benefit factor as well as additional adjustment factors to the ISSP context, namely the Facilitator factor as the human aspect and independent factor, namely the Culture factor. The research evaluation used a quantitative approach, with the distribution of questionnaires at an early stage to test the questionnaire as an instrument, and then continued with pretest and pilot test activities which produced instruments that had met the reliability and validity. The next stage is the distribution of the questionnaires and the data is filtered by purposive sampling technique with a total of 223 samples. Processing of this sample data used the Partial Least Square Structural Equation Modeling (PLS-SEM) method. Evaluation of statistical test results concluded that all factors have a significant role in the success of ISSP, but the effect and level of importance are different results. The factors that significantly influence the success of ISSP are the System Delivery Quality factor and the Culture factor. The system Delivery Quality factor is also a mediating factor with a significant influence on success. Other factors such as Facilitator, Satisfaction, Planning System Quality, Product Quality, Use factor and their combination have no significant effect on the success of ISSP. Based on the level of importance, it is also concluded that there are only three factors that have a high level of importance, namely Culture, System Delivery Quality and Satisfaction factors, while other factors have a low level of importance.